2018
DOI: 10.1136/archdischild-2017-313653
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in congenital heart disease surgery in children and young adults: a systematic review and meta-analysis

Abstract: CHD surgical patients have substantially worse HRQOL compared with age-matched healthy controls. Strategies should focus on improving HRQOL in this subgroup. Results may not be applicable to low/middle-income countries given the dearth of relevant research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 71 publications
2
48
0
1
Order By: Relevance
“…after palliative single ventricle surgical repair, remains lower than in CHD eligible to biventricular surgical repair (44), such as tetralogy of Fallot (34). As in our previous studies in older children, this study con rms the negative impact of repeated invasive cardiac procedures (surgery or catheterization) on HRQoL (10,51). Moreover, children with a CHD may suffer from an impaired physical capacity, which directly impacts the physical dimension of their HRQoL (6).…”
Section: Discussionsupporting
confidence: 74%
“…after palliative single ventricle surgical repair, remains lower than in CHD eligible to biventricular surgical repair (44), such as tetralogy of Fallot (34). As in our previous studies in older children, this study con rms the negative impact of repeated invasive cardiac procedures (surgery or catheterization) on HRQoL (10,51). Moreover, children with a CHD may suffer from an impaired physical capacity, which directly impacts the physical dimension of their HRQoL (6).…”
Section: Discussionsupporting
confidence: 74%
“…This result is surprising as other authors had described impaired HRQoL in children with isolated ARM 24,25 or congenital heart disease. 26 Additionally, it has also been shown that these concomitant anomalies are a major influential factor for reduced HRQoL in patients with a history of EA. 27,28 The reason why presence of ARM or congenital heart disease had no negative influence on HRQoL in our collective remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the results of the studies were a function of the instruments used or of the normative data available. For cardiac‐specific QoL, patients with complex heart defects had worse scores in the domains of symptoms, cognitive problems and treatment barriers than individuals with moderate or simple defects .…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, a literature review and meta‐analysis of 20 studies were published on health‐related QoL in children and young adults who had previously undergone cardiac surgery . Patients reported lower scores than healthy controls with regard to generic health‐related QoL, with the largest difference seen in physical functioning.…”
Section: Introductionmentioning
confidence: 99%